Secondary School Drop-Out Prevention Dormitory Program (Training and Practice : Journal of Educational Sciences, 2016)
The law for public education strongly enhances the importance of educational practices. Education is a primary focus in legislation, and dormitory-pedagogy may support and complement scholar education in several ways. In the long run the goal of the program is to support students living in dormitories in order to decrease early drop-out rates. The aim of the research is to find out the main reasons for leaving high schools before graduation in the frame of focus group interviews with students starting secondary school. Following the interviews we aim at highlighting the possibilities for change, which could prevent early drop-out. We would like draw the attention to the importance of effective cooperation between schools and dormitories and the outstanding role of pedagogues, especially foremasters.